TINGKAT PARTISIPASI MASYARAKAT KAMPUNG JAWA DESA TEBING LINGGAHARA BARU DALAM GERAKAN “RUMAH BELAJAR” MAHASISWA/I KKN KELOMPOK 185 UINSU PERSPEKTIF WAHDATUL ULUM - Abd Mukhsin; Aldita Ifani; Aulia Afiffah Br. Manurung; Dian Fatihani Situmorang; Patimah Rahayu Rambe (STIT AL-AMIN KREO TANGERANG, 2021)
Community participation in development in Tebing Linggahara Baru Village, West Bilah Subdistrict, Labuhanbatu Regency tends to have been implemented as a whole. Law No. 6 of 2014 mandates that village development planning must be carried out in a participatory manner and involve the entire community, including vulnerable groups (minorities, diffables, women, and the poor). It is intended that the development carried out by the village is truly beneficial for all residents. The impact of development planning that is not yet participatory is that the benefits of village development cannot be felt by all levels of society, so that development programs cannot be considered successful. Community development certainly cannot be separated from the problem of children's education. Coupled with the current pandemic conditions, many students from elementary school to high school are required to study online at home. This causes problems in the development of students' interest in learning, especially in the Javanese village of Tebing Linggahara Baru Village. As one of the efforts to realize participatory village development planning, KKN Group 185 students at UINSU Medan came with a work program that focused on children's education in the